Improving QoS and throughput in single- and multihop WLANs through dynamic traffic prioritization. - Iera, A. (IEEE Network : the magazine of global information exchange)
Nowadays, research efforts are being put into the design of effective mechanisms to provide service quality differentiation in IEEE 802.11-based wireless LANs. In this article we analyze the effects of augmenting the contention-based channel access mechanism of IEEE 802.11e through the assignment of dynamic traffic priorities, that adapt to either the application's quality requirements or the network congestion status. The aim is to show the effectiveness and robustness of the proposed dynamic mechanism in a wireless ad hoc network, in both single-hop and multihop scenarios, under variable traffic and network load conditions.